2015
DOI: 10.1177/0047287515569778
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Demand Spillovers between Australia and New Zealand

Abstract: International tourism is susceptible to fluctuations and shocks. The spillovers of international inbound tourism between Australia and New Zealand have been one of the key issues for both governments and tourism authorities to address. This paper used a bivariate GARCH model to investigate the spillovers of international tourist arrivals between Australia and New Zealand from seven countries (Canada, China, Germany, Japan, Korea, United Kingdom, and United States). The monthly international tourist arrivals be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Second, the GARCH methodology has been applied in the tourism literature to model the volatility of tourism demand (e.g. Balli and Tsui, 2015;Chan et al, 2005;Chang et al, 2011a;2011b;Shareef and McAleer, 2007;Song and Li, 2008). The empirical models of this study have revealed that the macroeconomic factors contributed at various levels to different markets, and the models we provided made fairly accurate forecasts for the visitors originating from the selected markets.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Second, the GARCH methodology has been applied in the tourism literature to model the volatility of tourism demand (e.g. Balli and Tsui, 2015;Chan et al, 2005;Chang et al, 2011a;2011b;Shareef and McAleer, 2007;Song and Li, 2008). The empirical models of this study have revealed that the macroeconomic factors contributed at various levels to different markets, and the models we provided made fairly accurate forecasts for the visitors originating from the selected markets.…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, in the New Zealand context, a substantial body of literature has discussed the international tourism demand (e.g. Balli and Tsui, 2015;Becken and Gnoth, 2004;Chan et al, 2005;Chang et al, 2011aChang et al, , 2011bTurner and Witt, 2001;Yeoman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al (2011) examined spillover effects of tourism demand for ASEAN countries to Taiwan. Balli and Tsui (2016) investigated interregional spillover effects for international tourism demand, such as Canada, China, Germany, Japan, Korea, United Kingdom, and United States to Australia and New Zealand.…”
Section: Literature Review Of Tourism Spillover Effectsmentioning
confidence: 99%
“…In New Zealand, international tourism has been the key driver of growth in its economy (and the largest export item) as well as the aviation sector makes significant contribution to its economy (Balli and Tsui, 2016;Becken, 2002;Becken et al, 2009;Duval, 2013;Tsui et al, 2017).…”
Section: Introductionmentioning
confidence: 99%